Pendidikan Bahasa Arab bagi Siswa Berkebutuhan Khusus Tuna Grahita di Madrasah Inklusi - Astuti, Erma Hari Tri; Khilmah, Khilmah; Marlika, Titim; Sa'adah, Nila (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Arabic language education for students with intellectual disabilities (ABK tunagrahita) in inclusive madrassas requires adaptive methods, effective media, and cross-stakeholder collaboration to achieve optimal outcomes. This study aims to analyze effective teaching methods, challenges faced by teachers, and the collaboration between teachers, parents, and therapists in teaching Arabic to ABK. Using a qualitative approach through literature reviews, the study found that individualization, multisensory, and demonstration methods are key to successful learning. Media such as flashcards, digital applications, and concrete objects help students grasp abstract concepts like Arabic letters. Major challenges faced by teachers include limited resources, insufficient specialized training, and communication barriers with students. However, effective collaboration among teachers, parents, and therapists enhances learning consistency and creates a supportive environment tailored to the individual needs of students. This study contributes to the development of inclusive Islamic education, particularly for students with intellectual disabilities.